القيم الأخلاقية في الأمثال العربية - يونس, علي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تناولت هذه الدراسة في مضمونها موضوع القيم الأخلاقية، ومدى انعكاسها في مقولات الأمثال العربية . خصوصاً بعدما اتضحت الوظيفة التي تؤديها الأمثال , بوصفها أداة معرفية مهمة, في نقل وتعليم هذه القيم التي تشكل ضمانة أكيدة لحماية المجتمع من مخاطر الوقوع في أتون التفسخ والانحلال والبغضاء . علماً أن هذا الترابط بين الأمثال وتعلّم القيم مرده إلى أن عبارة المثل سهلة وسريعة الحفظ والتداول , وعلاوة على ذلك إنها خلاصة مكثفة لتجارب الحياة حلوها ومرها , خيرها وشرها . فالمثل كما يقال يختزن في شموله ومضمونه عقل الأمة وفكرها . ولكن حتى لا يبقى البحث في إطاره النظري البحت, سعت الدراسة في إطار رصدها الجوانب الإيجابية والسلبية في منظومة القيم هذه , إلى توظيف عدد من الأمثال في هذا السياق , وبيان ما قالته في ذلك . In the content of this study, the subject of moral value, and the extent to which they are reflected in Arabic proverbs were examined. Especially after the role played by these proverbs became clear, as an important knowledge tool, in transferring and learning these values, which represent a sure guarantee for society protection from the dangers of falling in the midst of disintegration, decaying and hatred. However, this correlation between proverbs and values learning is due to that, proverbs are easy and can be handled and memorized quickly. Moreover, they are intensive summaries of life experiences, such as badness, goodness, decency and evilness. So, proverbs, as could be said, are stored in its comprises and content the mind of the nation and its ideology. But, to prevent this research from being in its purely theoretical framework, the study tried (within its framework of monitoring positive and negative aspects in this system of values), to employ a number of proverbs in this context, and explained what were said in them.